The effects of acute vitamin C supplementation on cortisol, interleukin-6, and neutrophil responses to prolonged cycling exercise - Davison, G.; Gleeson, M. (European Journal of Sport Science, 2007)
The depression of immune cell function that is typically observed after prolonged exercise is thought to be largely mediated by increased concentrations of stress hormones and cytokines as well as, possibly, oxidative stress. The aim of this study was to measure immunoendocrine responses, with acute vitamin C or placebo ingestion, before and during prolonged exercise. In a single-blind, randomized, counterbalanced/crossover design, eight healthy males ingested a bolus of 500 mg and 1000 mg vitamin C 2,5 h and 14 h pre-exercise respectively, then cycled for 2 h at approximately 60% maximal oxygen uptake (VO2max). They also consumed either placebo or vitamin C (1500 mg · l-1) beverages (2.5 ml · kg-1 body mass) every 15 min during exercise. Compared with the placebo trial, resting and post-exercise plasma vitamin C concentration and antioxidant capacity were higher and post-exercise oxidative stress markers were lower in the vitamin C trial. There was no difference between trials in the magnitude of post-exercise increases in circulating neutrophil numbers, plasma cortisol and interleukin (IL)-6 concentrations. There was a significant (2-way ANOVA) main effect of trial (P=0.039) and trial×time interaction (P=0.008) for PMA (phorbol-12-myristate-13-acetate)-stimulated chemiluminescence per neutrophil, with the post-exercise values significantly higher in the vitamin C trial (P<0.05). The results suggest that acute vitamin C supplementation may improve post-exercise neutrophil oxidative burst capacity. Given that there was no effect on cortisol, IL-6, and the circulating neutrophil count, a likely explanation is that acute vitamin C ingestion reduced (auto)oxidative "damage" to neutrophils, which could result in less impairment of their functional capacity after exercise.